The millicent quibb school of etiquette for young ladies of mad science ebook - McKinnon, Kate (The Millicent Quibb School of Etiquette for Young Ladies of Mad Science, 2024)
The #1 New York Times bestseller! From beloved Saturday Night Live legend Kate McKinnon comes a madcap adventure about three sisters, a ravenous worm, and a mysterious mad scientist! So, you want to be a young mad scientist. Congratulations! Admitting it is the first step. The second step is reading the (definitely true) tale of the Porch sisters…   Gertrude, Eugenia, and Dee-Dee Porch do not belong. They don’t belong in the snooty town of Antiquarium, where all girls have to go to etiquette school and the only dog allowed is the bichon frise. They don’t belong with their adoptive family, where all their cousins are named Lavinia and their Aunt has more brooches than books. And they certainly don’t belong at Mrs. Wintermacher’s etiquette school—they’re far more interested in science. After getting kicked out of the last etiquette school that would take them, the girls expect to be sent away for good... until they receive a mysterious invitation to new school.   Suddenly the girls are under the tutelage of the infamous Millicent Quibb—a mad scientist with worms in her hair and oysters in her bathtub. At 231 Mysterium Way, the pizza is fatal, the bus is powered by Gerbils, and the Dean of Students is a hermit crab.  Dangerous? Yes! More fun than they’ve ever had? Absolutely! But when the sisters are asked to save their town from an evil cabal of nefarious mad scientists, they must learn to embrace what has always made them stand out, and determine what side they’re on—before it’s too late!